TWITTER SEBAGAI MEDIA DAKWAH - Ahmad Fathan Hidayatullah (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Social media utilization by moslem community has increased from year to year. In the last decade, Facebook and Twitter are used as means of communication to forward the religious messages and Islamic preaching (dakwah). Among existing social media, twitter is considered having quite high popularity in society. Trend of conducting dakwah by twitter with kultwit apparently has assisted the Muslim preachers to deliver Islamic messages in more interesting way. Furthermore, they gain positive respond from society. Kultwit has become one of the alternative sources to obtain information about Islam and to understand Islam deeper.